Is acute ureteroscopy for painful ureteric colic cost effective and beneficial for patients? a cost-analysis. (January 2017) - Darrad, Maitrey; Sibartie, Tara; Inglis, John; Rukin, Nick
Introduction and objectives: Admissions for ureteric colic are relatively common, with up to 80% of stones passing spontaneously. In patients with refractory pain, drainage with stenting, percutaneous nephrostomy or stone removal can be performed. Due to the financial restrictions of the NHS, it is paramount to ensure patients are receiving optimal cost-effective care. We present a cost effectiveness analysis between primary ureteric stenting and emergency ureteroscopic stone removal in patients with refractory pain secondary to acute ureteric calculi. Methods: Fifty patients were analysed who underwent either primary ureteric stenting or emergency ureteroscopic stone removal in our institution. Each group contained 25 consecutive patients. The primary outcomes compared were: time to stone-free status, number of hospital re-admissions, and overall cost of treatment until stone free. Results: Both stenting ( n =25) and ureteroscopic stone removal ( n =25) groups were comparable with respect to age, sex, stone size and location. The hospital re-admission rate secondary to stone-specific issues was significantly lower in the ureteroscopy group, two versus 20. Patients became stone free significantly quicker in the ureteroscopy group (2.5 days vs. 61.9 days). The total overall cost until being declared stone free was significantly lower in the ureteroscopy group (£3104 vs. £4041, P ⩽0.001). Conclusions: This study highlights that those patients undergoing ureteric stenting take significantly longer to become stone free, leading to increased hospital re-admissions, potentially increased morbidity and inevitably greater cost implications. We advocate that primary ureteroscopic stone removal should be consider instead of ureteric stenting in patients with ongoing, painful ureteric colic.